Impact of electronic diabetes registry 'Meaningful Use' on quality of care and hospital utilization. (1st July 2015) - Han, Wencui; Sharman, Raj; Heider, Arvela; Maloney, Nancy; Yang, Min; Singh, Ranjit
Abstract: Objective To investigate whether the use of diabetes registries meeting Meaningful Use core objectives in primary care practices is associated with differences in quality of care and hospital utilization rates. Materials and methods A practice assessment survey was conducted to identify whether and how practices were using diabetes registries. Insurance claims data from 2010 were used to compare the health outcomes of patients from practices that used diabetes registries meeting Meaningful Use–related objectives to the outcomes of patients from other practices. Logistic hierarchical linear modeling was used to analyze the data. Results Records from 12, 514 diabetic patients (including 10 809 with type 2 diabetes) from 50 urban practices were included in the analysis. The results suggest that patients with type 2 diabetes who were treated in practices using registries for patient reminders were more likely to have completed the recommended laboratory testing (odds ratio [OR] 1.26, p < 0.01) and dilated retinal examinations (OR 1.14, p < 0.01). Patients in practices using registries for quality improvement were less likely to have 'avoidable hospitalization' (OR 0.83, p < 0.01) and emergency room visits (OR 0.76, p < 0.01). The use of a diabetes registry did not have a significant impact on the quality of care or hospital utilization for patients with type 1 diabetes. Conclusion Use of diabetes registries meeting Meaningful Use core objectives is associated with higher completion or recommended lab tests and a lower hospital utilization rate for patients with type 2 diabetes.